THE SUCCESFUL USE OF SAND CONSOLIDATION AT TUNU FIELD - Adhityas Vena Sasmita; Sisworini Sisworini; Reno Pratiwi (Fakultas Teknologi Kebumian dan Energi, Universitas Trisakti, 2020)
Oil and gas productions are demanded more these days. The industries itself have to be creative in many ways to increase the productions. The industries have to take the risk no matter what to fulfill these demands including trying a few methods. Some of the techniques are brand new and there is always a possibility that it decreasing a production instead of increasing.TUNU Field has one of the biggest gas productions in the world and it belongs to Pertamina Hulu Mahakam. It is located in Mahakam River Delta of East Kalimantan, Indonesia. For almost 80 kilometers it is spread from north to south of the Mahakam River Delta and covering about 400 square kilometers. The reservoirs are characterized as multilayered reservoirs with perforated producing zones ranging from (MD) 700 m to 5100 m.Sand production in well is one of the obstacles that oil industries are facing when it comes to oil and gas productions. There is of course limitation to sand production; it can bring benefits to good performance in a suitable amount. It can also be completely harmful to a well or in producing oil and gas. To prevent a sand breakthrough, sand control is put to the test. In this paper, a new technique of sand control will be discussed along with its advantages and disadvantages. This new method is called sand consolidation.Before sand consolidation being treated, some criteria have to match the standard. If it does not meet the criteria, it could mean either the reservoir does not need a sand control or using a mechanical sand control. When a reservoir is ready to be injected with the sand consolidation treatment, there is some procedure to follow. With the different type of sand consolidation chemicals, the temperature of the reservoir is important to this operation. One wrong chemical can lead to failure.In sand consolidation, the velocity gas and the drawdown are being reviewed due to managing risk of the well's integrity and good productivity. To control sand successfully, several important objectives must be reached during consolidation. The primary objective of sand consolidation is to bond together the formation sand adjacent to every perforation. Considering the treatment is designed to function on formation sand a zone several feet in radius around the wellbore can be consolidated.Studies of consolidation failure mechanisms show that plastics for the treatment must be inactive to reservoir fluids, should have very quick curing days and must have a robust wetting property. Including the gas flow rate increases after the treatment. Keyword: Sand Consolidation